E-Government Service for Driving Digital Creative Economy in Developing Region: Perspective of Technology Readiness Index and PLS-SEM - Rahmawati, Nanes Fitri; Inan, Dedi I.; Juita, Ratna; Indra, Muhamad (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2025)
E-government plays an important role in digital economic transformation by improving access to public services and driving economic growth. One implementation in West Papua Province is Rumahekraf, a digital marketing platform for creative economy players in the local region. However, the adoption of this platform is still low, and not many studies have examined factors that influence public acceptance of this service. Therefore, this study aims to identify factors that contribute to and inhibit users' intentions to adopt this platform in West Papua. We combine the Technology Readiness Index (TRI) and Technology Acceptance Model (TAM) to understand this phenomenon. Data was gathered via an online survey utilizing Google Forms, consisting of 157 merchants/business owners. The information was examined employing Partial Least Squares Structural Equation Modeling (PLS-SEM). The research indicates that innovativeness, perceived ease of use (PEOU), and facilitating conditions play an important role in increasing users’ intention to adopt Rumahekraf (R² = 59.4%). Additionally, PEOU also contributes to increased perceived usefulness (PU) (R² = 41.1%), which in turn strengthens the benefits perceived by users (R² = 55.7%). Optimism significantly affects PEOU but not usefulness. Meanwhile, insecurity and discomfort were not found to be major barriers to the adoption of this platform. This research provides insights for local government and platform development in improving the effectiveness of e-government implementation in West Papua by providing more adequate infrastructure and increasing public trust in the platform.